Implementation of the Problem based Learning Model to Enhance High Order Thinking Skills (HOTS): A Systematic Literature Review - Lingga, Leny Julia; Nusantara, Toto; Mashfufah, Aynin (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2024)
High Order Thinking Skills became the center of attention to achieve the goal, namely that students can think at a high level in any matter, one of which is by using learning models during the teaching and learning process. Therefore, this article discusses an overview of problem based learning and high order thinking skills (HOTS) learning models. This research applies the Systematic Literature Review (SLR) method by collecting data through POP (Publish or Perish) and ERIC. resulting in an initial database of 18,724 articles from ERIC and 116 articles from Scopus. Then the data was filtered based on descriptors with the keyword